The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1103/physrevlett.82.4256
|View full text |Cite
|
Sign up to set email alerts
|

Sum-Frequency Vibrational Spectroscopic Study of a Rubbed Polymer Surface

Abstract: Sum-frequency vibrational spectroscopy has been used to probe the chain orientation of polyvinyl alcohol at the surface after rubbing. The distribution function of the chain orientation is determined quantitatively. The orientational order parameter of the chains deduced from the distribution matches well with that of a liquid crystal monolayer deposited on the polymer, proving that the polymer surface can align a liquid crystal film through orientational epitaxy. [S0031-9007(99)09202-9] PACS numbers: 68.35.Bs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
186
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(190 citation statements)
references
References 17 publications
3
186
0
1
Order By: Relevance
“…Polymers are an important and commonly used material in the field of homogeneous alignment of LC molecules [1][2][3][4][5]. By unidirectionally rubbing a thin film of polymer with a fibrous material such as velvet, the molecular alignment for certain LCs can be promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are an important and commonly used material in the field of homogeneous alignment of LC molecules [1][2][3][4][5]. By unidirectionally rubbing a thin film of polymer with a fibrous material such as velvet, the molecular alignment for certain LCs can be promoted.…”
Section: Introductionmentioning
confidence: 99%
“…The theory behind SFG as a surface-sensitive spectroscopic technique and the analysis to obtain orientation of methyl and methylene groups has been discussed previously. [12][13][14][15][16][17][18][19] Here we summarize the main points to understand the work reported in this paper. The second-order nonlinear susceptibility can be expressed using a Lorentzian function with a resonance peak at ω q and width Γ q corresponding to a resonance mode q.…”
mentioning
confidence: 99%
“…The intensity, polarization, and resonance frequency of the SFG signal yield chemical and orientational information on molecules at interfaces. [12][13][14][15][16][17][18] Here, we compare the differences in the surface structure of 65 nm thick octadecyl polymer films prepared by spin-coating to a 7 nm polymer layer prepared by solution dipping on a mica substrate. In both cases, the SFG signals show strong methyl asymmetric and symmetric stretching vibrations indicating ordered methyl terminal groups.…”
mentioning
confidence: 99%
“…18,19 The rubbing process induces orientational order in polymer chains, and the relaxation of this order provides a sensitive probe of the relaxation process of the surface chains. 18,20 Although NEXAFS has excellent molecular sensitivity, it lacks a high enough signal-to-noise ratio to do rapid kinetic measurements of relaxation dynamics. On the other hand, past results have shown that the rubbing process also induces birefringence in polyimide films.…”
Section: Introductionmentioning
confidence: 99%